#TITLE_ALTERNATIVE# - JALU BRAMANTYA (NIM : 10104069); DosenPembimbing : Dr. Leo HariWiryanto, EDO
The objective of the research is to study a model for steady wave on ideal fluid over a symmetrical bump and to derive equations of model, and to find out the solutions of the model. The model of the research refers to Shen [2]. The results of the research are the equations for the zeroth, first, and second approximations. These equations is used to find out the equation and the solutions of forced KdV for h(x)=0 in x < -1 and h(x) ≠ 0 in -1 < x < 0. The solution of forced KdV for for h(x)=0 in x < -1 used system boundary integral equations. The solution of forced KdV for h(x) ≠ 0 in -1 < x < 0 used Runge-Kutta order 4 method.